THE EFFECT OF PHARMACOLOGY INTERACTIVE DIGITAL MEDIA IN THE FIELD OF INTEGUMENTARY SYSTEM ON THE LEVEL OF UNDERSTANDING AND MOTIVATION OF MEDICAL STUDENTS OF WIDYA MANDALA CATHOLIC UNIVERSITY - Purnama, Stephany Venesia; Novita, Bernadette Dian; Oenarta, Dave Gerald (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2025)
Technology plays an important role in education today. Conventional learning media, such as books, articles, journals, and other forms of literature, tend to make students less motivated to learn because they are often perceived as less interesting, monotonous, and boring. In contrast, technology-based learning makes the process more engaging and enjoyable. In medical education, many subjects are essential to understand, one of which is pharmacology. Pharmacology needs to be understood because knowledge in this field is used as the basis for selecting appropriate treatments for patients according to their clinical conditions. The aim of this study is to determine the effect of the use of pharmacology interactive digital media in the integumentary system on the level of understanding and motivation of medical students at the Faculty of Medicine, Widya Mandala Surabaya Catholic University. The number of samples in this study was 70 participants, with the results showing a p-value of 0.000. Therefore, it can be concluded that the H1 is accepted. The use of pharmacology interactive digital media in the integumentary system has a significant impact on the level of understanding and motivation of medical students at the Faculty of Medicine, Widya Mandala Surabaya Catholic University.